PEMILIHAN JENIS PELAYANAN DAN JENIS KERETA PADA URBAN RAILWAY YOGYAKARTA-MAGELANG - , HAPPY MARADINA, Prof. Ir. Sigit Priyanto, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The distance between Yogyakarta and Magelang distance which about 45 kilometers has a fairly high-intensity movements. It can be seen from the highway traffic conditions that have been crowded and saturated. Along some streets congested due to poor road conditions. Congestion does not only occur on weekdays but also during holidays, because the mobility of tourism activity in the two regions are also quite high. Therefore, mass transport needed to meet the level of passenger demand. Thatâs why there should be built urban railway Yogyakarta- Magelang. The study was conducted using a questionnaire interview with railway experts to determine the appropriate type of train of Yogyakarta-Magelang railway. The results of the interview are tailored to the basic techniques and theories that support in order to obtain the appropriate type of train. Determination the type of service appropriate to the type of train has been selected, itâs stated preference survey (questionnaires) to public. The questionnaire consists of 7 independent variables, namely: the capacity of the train, train classes, facilities, stations / shelter, travel time, the estimated rates, and rating options, as well as a dependent variable (the type of train). Four hundred questionnaires distributed and 349 questionnaires were analyzed. Data from questionnaires were analyzed first with a descriptive analysis in order to know the description and the validity of the data. Then it analyzed by the Multinomial logit model (MNL), so the appropriate type of service obtained. The results of survey interviews with railway is experts Rail Diesel Trains (KRD) for Yogyakarta-Magelang railway. The analysis of the MNL produce a selection of trains with the service standard of 81.6%, types of trains with good service by 77%, and the type of train with tourism services at 80.7%. It can be concluded that service users prefer to the standard of service, ie the travel time of 1hr, the estimated rate of Rp 10,000, - and the economy class without AC.